General, organic, and biological chemistry : - Timberlake, Karen (Benjamin Cummings, 2002)
General, Organic, and Biological Chemistry provides a readable, uncomplicated and accessible introduction to students in allied health and other fields who have little or no background in chemistry. Timberlake uses the same style and integrated pedagogy that have made her one-semester text so successful in the classroom. She balances technical accuracy and everyday examples to help bring chemistry to life for students.